Knowledge gaps and rural development in Tajikistan: Agricultural advisory services as a panacea? - Anastasiya Shtaltovna (University of Bonn, Center for Development Research (ZEF), 2013)
In this paper I look at knowledge systems and the channels of innovation diffusion in Tajikistan. In particular I look at the formation of the agricultural advisory services as a vital source of knowledge and innovation for farmers during the transition process. After the end of the Soviet Union and the civil war in Tajikistan, the knowledge available to farmers can be described as a mix of, on the one hand, traces and fragments originating from the Soviet agricultural and educational system represented by the universities, research institutes and academy of sciences; and on the other hand, western-style knowledge, mainly introduced by development agencies. The paper analyses the functioning of and interaction between the international donors, NGOs, Tajik government and academic institutions. Donors are relatively new actors in the field of knowledge dissemination, but important ones. In this paper I show how under the framework of 'development', i.e. the rhetoric, organization and infrastructure of development, different donors play their own games, some of them geo-political. At the same time they provide support for the functioning of local NGOs and help them to sustain; also donors are used by the Tajik political actors for their own purposes. From this discussion I derive suggestions on how agricultural advisory services could be organized in Tajikistan, working on some local weaknesses and building on existing assets, traditions and networks, reflecting the interplay of the main actors and local needs.
Keywords: 330; agricultural advisory services; extension; knowledge; innovation; rural development; development cooperation; Tajikistan; Central Asia